Socio-cognitive correlates of primary school children's deceptive behavior toward peers in competitive settings - Narcisa Prodan; Xiao Pan Ding; Raluca Diana Szekely-Copîndean; Andrei Tănăsescu; Laura Visu-Petra (Acta Psychologica, 2023)
Competing for limited resources with peers is common among children from an early age, illustrating their propensity to use deceptive strategies to win. We focused on how primary school-age (6–8 years old) children's strategic deception toward peers is associated with their socio-cognitive development (theory of mind and executive functions). In a novel computerized competitive hide-and-seek game, we manipulated the peer opponents' familiarity (familiar vs. unfamiliar) and actions (following vs. not following children's indications), as well as the stimuli likability (liked vs. disliked cards). Our findings demonstrated that children deceived the familiar opponent less than the unfamiliar one, indicating their determination to preserve positive peer interactions. We showed that theory of mind and executive functions significantly predicted children's willingness to deceive. Notably, second-order false belief understanding and visuospatial working memory positively predicted children's use of truths to deceive, whereas inhibitory control and cognitive flexibility efficacy scores were negatively related to their deceptive performance when using the same strategy. Implications for children's competitive behavior toward peers involving lie-telling are discussed.